Giant Pelvic Cocoon with Intra Prostatic Extension (Intravesical Tortoise!!!!!!!) - Mylarappa, Prasad; Amey, Pathade; Shetty, Prathvi; Sandeep, Puvvada; Banale, Kailash B; Ramesh, D (Asian Journal of Medical Sciences, 2013)
Giant vesical calculus is a rare clinical entity in the recent urological practice. Males are affected more than the females. We report a case of 55years old male patient non diabetic or hypertensive who presented with urinary symptoms. His biochemical parameters were within normal limits. Urine analysis and culture sensitivity showed infection. His ultrasonography revealed a giant vesical calculus with intra prostatic extension and bilateral hydroureteronephrosis and small prostate. After controlling the urinary infection with course of antibiotics, he underwent an open cystolithotomy and post-operative recovery was uneventful. DOI: http://dx.doi.org/10.3126/ajms.v3i4.7160 Asian Journal of Medical Science Vol.3(4) 2012 pp.47-49